Real-time intraoperative OCT imaging of the vitreolenticular interface during pediatric cataract surgery. Issue 9 (September 2021) - Sillen, Hedwig; Van Looveren, Jan; Plaeke, Philip; Van Os, Luc; Tassignon, Marie-José
Abstract : This study demonstrated that intraoperative OCT images improves the understanding of VLI dysgenesis in pediatric cataract and helps the surgeon to anticipate difficulties that can be encountered during surgery. Abstract : Purpose: To report on the use of intraoperative optical coherence tomography (OCT) imaging of the vitreolenticular interface (VLI) during pediatric cataract surgery and to determine the incidence of VLI dysgenesis and surgical difficulties. Setting: Department of Ophthalmology, Antwerp University Hospital, Edegem, Belgium. Design: Retrospective cohort study. Methods: This study included 51 pediatric patients who underwent cataract surgery between April 2016 and December 2018. Video recordings and OCT images of the VLI were analyzed and compared. VLI dysgenesis was considered present when intraoperative OCT images demonstrated partial or total adhesions between the posterior lens capsule and the anterior hyaloid membrane. Video recordings were analyzed to describe surgical difficulties, more specifically: inability to create a calibrated primary posterior continuous curvilinear capsulorhexis (PPCCC), occurrence of vitreous prolapse, need for anterior vitrectomy, and complicated IOL implantation. Results: Of the 51 patients included, VLI dysgenesis was demonstrated in 27 patients (52.9%). The incidence of VLI dysgenesis was greater in children with unilateral cataract (72.4%), and children with a posterior capsule plaque (90%). PPCCC was challenging in 20 patients. A defect of the anterior hyaloid membrane was found in 16 patients. Anterior vitrectomy or cutting vitreous strands with scissors was necessary in 10 patients. Conclusions: Intraoperative OCT images were an excellent tool to evaluate the VLI and to demonstrate the presence of VLI dysgenesis during pediatric cataract surgery. Performing a calibrated PPCCC was more challenging in the presence of VLI dysgenesis. This can subsequently expose a defect in the anterior hyaloid membrane, which may result in vitreous prolapse.